Heavy metal pollution and health risk assessment of agricultural land in the Southern Margin of Tarim Basin in Xinjiang, China. Issue 7 (3rd October 2021) - Fan, Wei; Zhou, Jinlong; Zhou, Yinzhu; Wang, Songtao; Du, Jiangyan; Chen, Yunfei; Zeng, Yanyan; Wei, Xing
ABSTRACT: The study aimed to analyze the level of heavy metal pollution in the agricultural lands in the southern margin of Tarim Basin, Xinjiang, and its risks to human health. A total of 1765 soil samples were collected from the Cele-Ruoqiang area. The contents of soil As, Cd, Cr, Cu, Hg, Ni, Pb and Zn were analyzed using the pollution load index method. The results showed that soil was slightly contaminated with Hg and Cd; the multivariate statistical analysis indicated that Cr, Ni, As, Cu, Zn, and Cd were formed mostly by geochemical genesis, whereas Hg and Pb contents by the geological origin and human activities. The health risk assessment showed that there is no unacceptable non-carcinogenic health risk. As levels posed carcinogenic risk, however, they were within human tolerance. Thus, this study provides a scientific basis for local agricultural production safety and prevention and control of soil heavy metal pollution.